Radical Hydro‐Fluorosulfonylation of Unactivated Alkenes and Alkynes. Issue 39 (25th August 2022) - Wang, Peng; Zhang, Honghai; Zhao, Mingqi; Ji, Shuangshuang; Lin, Lu; Yang, Na; Nie, Xingliang; Song, Jinshuai; Liao, Saihu
Abstract: Recently, radical fluorosulfonylation is emerging as an appealing approach for the synthesis of sulfonyl fluorides, which are highly in demand in various disciplines, particularly in chemical biology and drug discovery. Here, we report the first establishment of radical hydro‐fluorosulfonylation of alkenes, which is enabled by using 1‐fluorosulfonyl 2‐aryl benzoimidazolium (FABI) as an effective redox‐active radical precursor. This method provides a new and facile approach for the synthesis of aliphatic sulfonyl fluorides from unactivated alkenes, and can be further applied to the late‐stage modifications of natural products and peptides, as well as ligation of drugs in combination with click chemistry. Remarkably, this system could enable the radical hydro‐fluorosulfonylation of alkynes, affording valuable alkenylsulfonyl fluoride products with a rare, high Z ‐selectivity, which are normally less stable and more challenging to synthesize in comparison with the E ‐configured products. Abstract : Radical hydro‐fluorosulfonylation of olefins has been successfully achieved by employing FABI as a FSO2 ‐radical precursor and ODA as an organic photocatalyst. With this photocatalytic system, radical hydro‐fluorosulfonylation of alkynes can also be realized with a unique, high Z ‐selectivity. Utilization of this method is further demonstrated in the late‐stage modification of natural products and drug ligation chemistry.